Literasi Hak Konstitusional Memperoleh Bantuan Hukum Gratis melalui Administrasi Kependudukan di MAN 4 Pekanbaru - Andrizal Andrizal; Eddy Asnawi Eddy; Tatang Suprayoga Tatang; Wilmar Redixon Lumban Gaol Wilmar; Zulhian Sultan Javari (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2026)
The low level of legal literacy has resulted in many students at Madrasah Aliyah Negeri (MAN) 4 Pekanbaru having limited understanding of their constitutional right to obtain free legal aid, particularly for economically disadvantaged citizens, as well as the importance of civil registration documents as a prerequisite for accessing such services. This community service program aimed to enhance students’ knowledge and understanding of the constitutional right to free legal aid and the civil registration requirements necessary to access legal assistance. The target participants were students from low-income families residing in Muara Fajar Village, Rumbai District, and surrounding areas who are vulnerable to legal issues arising from juvenile delinquency, including drug abuse, gang violence, and theft. The program was implemented through legal education sessions, lectures, and interactive discussions, with participants' learning outcomes evaluated using pre-test and post-test assessments. The partner institution actively supported the program by providing the venue, coordinating participants, and facilitating the implementation of activities. The findings demonstrated a significant improvement in participants’ understanding of the constitutional right to free legal aid, eligibility criteria, and the required civil registration documents. Furthermore, the program strengthened students’ legal awareness and encouraged the appropriate utilization of government-funded legal aid services. The outputs of this program include enhanced community legal literacy, scientific publication, and the dissemination of community service outcomes as part of the implementation of the university's Tri Dharma responsibilities.